Evaluation of the AccessIT Project and the Distance LearningProgramme on Digitization - Bülent Yılmaz; Özgür Külcü; Yurdagül Ünal; Tolga Çakmak (Türk Kütüphaneciliği)
AccessIT is an EU-funded project under EU’s Education and Culture Program aiming to digitize a certain amount of sources that are part of the cultural heritage, to transfer them to Europeana, and to sustain the education infrastructure to achieve this goal in the partner countries of Greece, Poland, Serbia, Turkey and UK. In this study, in addition to the general evaluation of the AccessIT Project, it is aimed to investigate the awareness of participants in thefield on digitization and digital content management, their self-efficiency perceptions, and to evaluate the education program based on the data acquired from the survey of544participants who were enrolled in the distance education program offered within the scope of the project.It was found out in the study that the AccessIT Project has had an important function in Turkey and the distance education program significantly contributed to participants ’ self-efficiency perceptions about digitization.